Programma: 12 mei Albert King; 15 mei Butch Hancock, Jimmie Dale Gilmore; 16 mei Arturo Sandoval y su grupo; 17 mei Giora Feidman
Programma: 12 mei Albert King; 15 mei Butch Hancock, Jimmie Dale Gilmore; 16 mei Arturo Sandoval y su grupo; 17 mei Giora Feidman.